2018
DOI: 10.1002/pd.5354
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected finding of uniparental disomy mosaicism in term placentas: Is it a common feature in trisomic placentas?

Abstract: ObjectiveNon‐invasive prenatal testing (NIPT) detects placental chromosome aberrations. When amniocentesis reveals a normal karyotype, confined placental mosaicism (CPM) may be assumed. In order to confirm this, placental cytogenetic studies were performed.MethodNIPT was conducted in the course of the Dutch TRIDENT study. Placentas of 10 cases with NIPT results indicating an autosomal trisomy and showing a normal (N = 9) or low mosaic karyotype (N = 1) in amniotic fluid (AF) were investigated. The cytotrophobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…Cytogenetic investigations of parental blood was performed with the same SNP array or with karyotyping (depending on the chromosome aberration). To identify the parental origin of the segmental uniparental disomy of chromosome 13 in case 2, SNPs were compared between mother and fetus as described previously …”
Section: Methodscontrasting
confidence: 63%
See 2 more Smart Citations
“…Cytogenetic investigations of parental blood was performed with the same SNP array or with karyotyping (depending on the chromosome aberration). To identify the parental origin of the segmental uniparental disomy of chromosome 13 in case 2, SNPs were compared between mother and fetus as described previously …”
Section: Methodscontrasting
confidence: 63%
“…Moreover, in one of the three placentas (case 2), cytogenetic studies revealed an extra chromosome aberration (a mosaic duplication of the short arm of chromosome 4) in one CTB biopsy that was not seen prenatally (with NIPT or invasive testing). This phenomenon of extra chromosome anomalies in the placenta was recently described in 2/10 placentas that were investigated in order to confirm abnormal NIPT involving a numerical chromosome aberration …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Trisomy, which is the most frequent chromosomal abnormality in humans and the leading cause of spontaneous abortions, is essentially linked to chromosome mis‐segregation at the maternal meiosis with the risk for a trisomic conceptus increasing with the increase of maternal age (Franasiak et al., ; Nagaoka, Hassold, & Hunt, ). Trisomy rescue, reported in no less than 1–2% of first trimester invasive prenatal diagnosis (Hahnemann & Vejerslev, ; Kalousek & Vekemans, ) and considered responsible for most false positive results by noninvasive prenatal screening (Hartwig, Ambye, Sorensen, & Jorgensen, ; Van Opstal et al., ) may save some of the embryos otherwise fated to be spontaneously aborted, leading to confined placental mosaicism where the abnormal cell line theoretically is isolated to the placenta and missing from amniotic cells or other fetal tissues. A probably less frequent phenomenon is a partial trisomy rescue in which only a part of the original trisomic chromosome is eliminated while a part remains, more often in the form of a supernumerary marker, in mosaic with a normal cell line.…”
Section: Reconstruction and Formation Mechanisms Of Ssmcmentioning
confidence: 99%
“…Trisomy rescue is likely to be the evolutionary trade‐off to compensate for the massive loss of embryos caused by the high level of aneuploidy of human female gametes. The push toward elimination of the supernumerary chromosome must be elevated at least in the early stages of early embryogenesis, as suggested by the demonstration of multiple rescue events in 3 out of 10 placentas from newborns with autosomal trisomy at the NIPT (Van Opstal et al., ). However, the rarity with which the loss of the supernumerary chromosome is estimated to occur in healthy people (King et al., ; Robinson, ) indicates that this event, although providing a rescue from deleterious conditions, has no evolutionary advantage and reinforces the idea that meiotic nondisjunction in human females and the consequent aneuploidy leading to implantation failure and early miscarriage, is under Darwinian pressure.…”
Section: Reconstruction and Formation Mechanisms Of Ssmcmentioning
confidence: 99%